Characteristics of the equatorial plasma drifts as obtained by using Canadian Doppler ionosonde over southern tip of India - Sripathi, S.; Singh, Ram; Banola, S.; Sreekumar, Sreeba; Emperumal, K.; Selvaraj, C. (My University, 2016)
We present here characteristics of the Doppler drift measurements over Tirunelveli (8.73°N, 77.70°E; dip 0.5°N), an equatorial site over Southern India using Doppler interferometry technique of Canadian ionosonde. Three-dimensional bulk motions of the scatterers as reflected from the ionosphere are derived by using Doppler interferometry technique at selected frequencies using spaced receivers arranged in magnetic E-W and N-S directions. After having compared with Lowell’s digisonde drifts at Trivandrum, we studied the temporal and seasonal variabilities of quiet time drifts for the year 2012. The observations showed higher vertical drifts during post sunset in the equinox followed by winter and summer seasons. The comparison of Doppler vertical drifts with the drifts obtained from (a) virtual height and (b) Fejer drift model suggests that Doppler vertical drifts are relatively higher as compared to the drifts obtained from model and virtual height methods. Further, it is seen that vertical drifts exhibited equinoctial asymmetry in prereversal enhancement quite similar to such asymmetry observed in the spread F in the ionograms and GPS L band scintillations. The zonal drifts, on the other hand, showed westward during daytime with mean drifts of ~150–200 m/s and correlated well with equatorial electrojet strength indicating the role of E region dynamo during daytime, while they are eastward during nighttime with mean drifts of ~100 m/s resembling F region dynamo process. Also, zonal drifts showed large westward prior to the spread F onset during autumn equinox than vernal equinox, suggesting strong zonal shears which might cause equinoctial asymmetry in spread F.
Keywords: Tirunelveli; Plasma drifts; CADI ionosonde; Doppler drift measurements; Canadian ionosonde; Equatorial plasma drifts